Perception Towards Joint Forest Management Programme in Conservation of Forest Resources in Jammu Division - Iqbal, Tariq; Slathia, PS; Peshin, Rajinder; Sehgal, Sandeep; Sharma, Manish Kumar; Kour, Kiran; Kumar, Rakesh (Indian Journal of Extension Education, 2020)
The present study was conducted in purposively selected â€œEast Forest Circleâ€ of Jammu division of J&K. Multistage sampling plan was followed for the selection of respondents. Six forest ranges from East circle having maximum number of JFMCs were selected purposively. Twenty four committees, four from each selectedÂ ranges of East circle and eight members from each selected JFMC were selected through random samplingÂ technique making the sample size to 192 respondents. The perception measurement consisted of 26 items. Results of quasi- experimental research design showed that majority of JFMCâ€™s members were agreed with all the perception statements except that JFM activities helps in increasing the agriculture yield/land productivity, promotes forest tourism and helpful in improving communication skills of participants.